Evaluation of the agroecological performance of productive systems in the diversity and life belt, Yasuní (III International Congress of Biotechnology and Neotropical Ecosystems, 2026)
The study was conducted in the Diversity and Life Belt (FDV), located near Yasuní National Park—an area affected by the expansion of the agricultural frontier. The objective was to evaluate the agroecological performance of the productive systems present in the FDV to determine their level of transition toward sustainability. The FAO’s TAPE tool was applied, allowing for the characterization of seven types of productive systems, differentiated as agricultural, livestock, and subsistence-based. The analysis considered five dimensions: economic, environmental, social, nutritional, and governance. The results showed that subsistence systems, particularly the Waorani chakra, achieved advanced levels of agroecological transition with better multidimensional performance, whereas the rest of the systems remained in early stages. It was concluded that agroecology represents a key alternative to curb agricultural expansion, strengthen local resilience, and restore the protective function of the FDV.